Optimasi Metode Pembuatan Self-Nanoemulsifying Drug Delivery System (SNEDDS) Ekstrak Jahe Emprit (Zingiber Officinale Var Arrum): Optimization of Self-Nanoemulsifying Drug Delivery System (SNEDDS) Manufacturing Method for Emprit Ginger Extract (Zingiber Officinale Var Arrum) - Salsabiela Dwiyudrisa Suyudi; Rissa Laila Vifta (Journal of Holistics and Health Sciences, 2025)
Antioxidant activity of Ginger Emprit (Zingiber Officinale Var Arrum) with the presence of flavonoid compounds with low solubility and permeability characteristics that can be overcome with self-nanoemulsifying drug delivery system (SNEDDS). The purpose of this study is to determine the effect of speeds using a high-pressure homogeniser on the characteristics of SNEDDS Ginger Emprit (Zingiber Officinale Var Arrum). The method of preparation was carried out with a mixture of VCO, Tween 80, and PEG 400 (1:5:1) and Emprit Ginger Extract at speeds of 5000, 10,000 and 15,000 rpm for 15 minutes. The analysis of the result was carried out statistically using SPSS ANOVA the Kruskal-Wallis test and Mann-Whitney test. The characteristics of SEDDS are seen from the particle size, PDI value, transmittance percentage, and emulsification time. The results showed that the SNEDDS preparation had emulsification times of 9.767 seconds, 13.903 seconds, and 6.126 seconds, particle sizes of each formula is 129.326 nm, 265.20 nm, and 279.60 nm, transmittance percentages of each formula is 46.658%, 23.729%, and 23.575%, and polydispersity index values are 0.964, 0.822, and 0.554. The results of statistical analysis showed that there was a significant difference between speeds of 10.000 rpm and 15.000 rpm.   ABSTRAK Aktivitas antioksidan jahe emprit (Zingiber Officinale Var Arrum) dipengaruhi oleh senyawa flavonoid dengan sifat kelarutan dan permeabilitas yang rendah sehingga dapat diperbaiki dengan sistem penghantaran SNEDDS. Tujuan penelitian ini untuk mengetahui pengaruh kecepatan pembuatan menggunakan homogenizer tekanan tinggi terhadap karakteristik SNEDDS Jahe Emprit. Metode pembuatan dilakukan dengan mencampurkan VCO, Tween 80, dan PEG 400 (1:5:1) dan Ekstrak Jahe Emprit pada kecepatan 5000, 10.000 dan 15.000 rpm selama 15 menit. Analisa Hasil Pengujian dilakukan secara statistika menggunakan SPPS ANOVA dan uji Kruskal-Wallis dan Mann-Whitney. Karakteristik SNEDDS dilihat dari ukuran droplet, nilai PDI, persen transmitan, dan waktu emulsifikasi. Hasil menunjukkan bahwa sediaan SEDDS memiliki waktu emulsifikasi 9,767 detik, 13,903 detik, dan 6,126 detik, ukuran droplet masing-masing formula 129,326 nm, 265,20 nm, dan 279,60 nm, persen transmittan masing-masing formula 46,658%, 23,729%, dan 23,575%, dan nilai indeks polidispersitas adalah 0,964, 0,822, dan 0,554. Hasil analisa statistika menunjukkan terdapat perbedaan signifikan antara kecepatan 10.000 rpm dan 15.000 rpm